Formation of the hurricane eye - Vigh, Jonathan L., author; Schubert, Wayne H., advisor; Cotton, William R., 1940-, committee member; Ito, Takamitsu, committee member; DeMaria, Mark, committee member; Krueger, David A., committee member (Colorado State University. Libraries, 2010)
This dissertation consists of three distinct studies which investigate aspects of eye formation. The first study reviews eye phenomenon in a variety of vortices ranging from simple vortices to the menagerie of geophysical vortices, emphasizing similarities and differences to the eyes formed in hurricanes. The hurricane eye is found to be a paradoxical structure imposed by conservation of angular momentum and the boundaries of the vortex. A comprehensive definition for hurricane eye formation is proposed and various eye formation mechanisms are summarized. The next study presents a simple theoretical argument to isolate the conditions under which a tropical cyclone can rapidly develop a warm-core thermal structure and subsequently approach a steady state. The theoretical argument is based on the balanced vortex model and, in particular, on the associated transverse circulation equation and the geopotential tendency equation. The transverse circulation and the temperature tendency in a tropical vortex depend not only on the diabatic forcing, but also on the spatial distributions of the static stability, the baroclinity, and the inertial stability. The vortex response to diabatic heating depends critically on whether the heating occurs in the low inertial stability region outside the radius of maximum wind or in the high inertial stability region inside the radius of maximum wind. This result suggests that rapid intensification is favored for storms which have at least some of the eyewall convection inside the radius of maximum wind. The development of an eye partially removes diabatic heating from the high inertial stability region of the storm center, yet rapid intensification may continue if the eyewall heating continues to become more efficient. As the warm core matures and static stability increases over the inner core, conditions there become less favorable for deep upright convection and the storm tends to approach a steady state. The final study characterizes the kinematic and thermodynamic changes that occur before, during, and after the initial eye formations of a broad set of Atlantic tropical cyclones. To obtain the requisite structure and intensity parameters, a new data set has been synthesized from the Vortex Data Messages transmitted by routine aircraft reconnaissance from 1989-2008. Intensity ranges are determined for the times when the eye/eyewall structure first appears in aircraft radar and infrared satellite imagery. The mean intensity at which an eye is first observed in both aircraft or satellite imagery is found to be 58 kt, somewhat lower than reported in previous studies. Changes about the time of eye formation are examined for intensity, the radius of maximum winds, the minimum Rossby radius of deformation, eye temperature and dew point temperature depression. Storms are found to intensify most rapidly near the time of eye formation, especially when a persistent eye is observed in infrared satellite imagery. Many storms which are forming eyes are found to undergo a substantial and rapid contraction in the radius of maximum winds during the 24-h period before the eye is observed; once the eye is present, this contraction slows or ceases. Strong warming at lower levels (850 or 700 hpa) of the eye is not observed to correlate well with the time in which the eye is first observed. Finally, observations suggest that the dynamical heating efficiency of the resulting eyewall increases even as the physical scale of the efficient heating region decreases. This allows the storm to continue intensifying even though the total inner core diabatic heating may decrease. The answer to why some storms fail to form eyes may shed light on whether eye formation is a stochastic process involving constructive and destructive mesoscale interactions -- or whether it is a manifold attractor of the system sometimes stymied by an unfavorable environment.
Department Head: Richard Harlan Johnson.